A study on the corrosion of stainless steel floor drains in an indoor swimming pool. (July 2017) - Szala, Mirosław; Beer-Lech, Karolina; Walczak, Mariusz
Abstract: This paper investigates the causes of pitting corrosion of stainless steel floor drains installed in an indoor swimming pool in a leisure and hotel complex. After a few months of service, corrosion pits were noted on the floor drain's surface. The chemical composition of the drain specified by the manufacturer indicates that it is made of X2CrNiMo17-12-2 (1.4404) stainless steel. An analysis of the chemical composition of the floor drains revealed that the Mo, Cr and Ni contents are in a low-range for this grade of stainless steel according to the PNEN 10088-2 standard. The results of the chemical composition analysis in microareas by the EDS method point to the concentration of chlorine and chlorine compounds on the surface. To measure corrosion damage, the corroded and uncorroded surfaces of the drain are measured by a contact profilometer and compared. The environment conditions of swimming pool water are examined. The results as well as a literature survey show that this grade of steel is not sufficiently corrosion-resistant for this type of application in a highly corrosive environment of indoor swimming pools, especially regarding components which are not regularly cleaned. The results of roughness tests of the drain surface indicate that roughness is another factor leading to corrosion. Drains should be manufactured from polished surface finish metal sheet. To avoid the risk of corrosion in the future, the unsuitable grade of steel should be replaced by a higher-alloyed stainless steel grade. Highlights: A case study of floor drain failure in an indoor swimming pool is presented. The influence of operational conditions on the stainless steel's corrosion is shown. The chemical composition of stainless steel affects its corrosion resistance. The application of 1.4404 steel for floor drains does not meet operation requirements.